Productive performance of crossbred Holstein x Jersey cows compared to Holstein straightbred cows (Revista de Ciências Agroveterinárias, 2013)
Milk production in temperate and subtropical climates is mostly based on pure bred cows. Changes in the value of milk composition of the marketed milk, as well as research efforts in countries with highly developed dairy farming with the use of crossbreeding between specialized dairy breeds, has made the practice of crossbreeding of Holstein and Jersey breeds more popular in southern Brazil. The objective of this study was to compare production of crossbred Holstein x Jersey compared to purebred Holstein. The assessments were carried out from data collected in three dairy farms in the states of Santa Catarina and Paraná. Crossbred Holstein x Jersey cows had lower milk yield in a 305 day lactation period (p
Keywords: Crossbreeding; Milk composition; Milk yield; Dairy specialized breeds.